The Temperament of School Aged Children who Stutter: Their View. (30th June 2015) - Nicholas, A.; Yairi, E.; Mangelsdorf, S.; Jiang, M.; Cook, F.
Abstract: Empirical studies concerning the temperament of school aged children who stutter (CWS) have been limited. CWS (aged 6 to 12) have been found to be more sensitive and withdrawn compared to their non-stuttering peers (Fowlie& Cooper, 1978; Oyler&Ramig, 1995) more anxious and introverted (Fowlie& Cooper, 1978) and less likely to take risks (Oyler, 1996). The questionnaires used in these studies involved parents making global judgements about their child rather than asking them to rate behaviours and reactions in specific situations. Given thenature of these questionnaires, parents' ratings may have been influenced by common stereotypes of the temperament of a child who stutters, which may be stronger given the longer stuttering history of older children. While children's temperament has typically been measured using parent ratings, self-report isalso considered to be an important source of information, particularly when investigating older children's temperament. A significant part of temperament refers to internal and hidden reactions and tendencies that are not easily observable to others and therefore would not be measured via observational methods (Carver &Scheier, 1996; Matthews, Deary& Whiteman, 2003; Muris et al., 2007). Children at age 7 and older seem to be able to reliably report about their own attributes, feelings, behaviours, and experiences (Danielson & Phelps, 2003;Measelle, John, Ablow, Cowan, & Cowan, 2005) and while parents tend to be better reporters of external behaviour, children are more accurate at conveying internal feelings, states and moods(Goodman, Ford, Simmons, Gatward, & Meltzer, 2000; Wrobel&Lachar, 1998). Using acomputerized self-report measure Simonds and Rothbart (2006) demonstrated that 7- to 10-year-olds were able to reliably report on their own temperament. The current study aims to investigate the temperament of children who stutter (CWS) and children who do not stutter (CWNS) aged 9:0 to 14:11 using a self-report questionnaire. Temperament was assessed using the Early Adolescent Temperament Questionnaire –Revised (EATQ-R) (Ellis &Rothbart, 2001). This questionnaire conforms to the reactive and self regulative model of temperament as presented by Rothbart and colleagues (Rothbart& Bates, 1998; Rothbart&Derryberry, 1981) and respondents are required to rate behaviours and reactions in specific situations (e.g., "I get angry quickly when teased") rather than make global judgements about themselves e.g. "I am kind"). Items have been worded in a simple and straightforward manner as to limit misinterpretation. Data will be presented comparing CWS and CWNS on three broad temperament factors of 'Effortful Control', 'Negative Affect, and 'Surgency'. Additionally, the individual temperament dimensions of Activation Control, Activity, Affiliation, Attention, Fear, Frustration, Surgency/High Intensity Pleasure, Inhibitory Control, Perceptual Sensitivity, Pleasure Sensitivity, and Shyness will be examined along with two behavioural scales, namely Aggression and Depressive Mood. Findings will be presented in the context of current research and clinical implications.